2016
DOI: 10.1021/acs.langmuir.6b01579
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-Induced Lamellar Gel Phases in Fluid Cell Lipid Extracts

Abstract: The effects of increasing amounts of palmitoylceramide (pCer) on human red blood cell lipid membranes have been studied using atomic force microscopy of supported lipid bilayers, in both imaging (bilayer thickness) and force-spectroscopy (nanomechanical resistance) modes. Membranes appeared homogeneous with pCer concentrations up to 10 mol % because of the high concentration of cholesterol (Chol) present in the membrane (∼45 mol %). However, the presence of pCer at 30 mol % gave rise to a clearly distinguishab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 70 publications
1
25
0
1
Order By: Relevance
“…It has been observed in many systems, including RBC lipids 24 , 29 , that Cer can give rise to rigid domains in the RBC membranes. In order to confirm that this was the case with our samples, RBC were incubated overnight with Pb(II) and the corresponding lipid extracts dispersed in buffer and analysed by differential scanning calorimetry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed in many systems, including RBC lipids 24 , 29 , that Cer can give rise to rigid domains in the RBC membranes. In order to confirm that this was the case with our samples, RBC were incubated overnight with Pb(II) and the corresponding lipid extracts dispersed in buffer and analysed by differential scanning calorimetry.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of non-purely ceramidic gel domains under saturating conditions is also possible and gel phases containing both ceramide and cholesterol can appear if both lipids are saturating the membrane 27 , 28 which could be the case for RBC membranes under Pb 2+ stress. A recent study from our laboratory demonstrated that RBC lipid extracts in the presence of high concentrations of ceramide exhibit lamellar gel domains enriched in both cholesterol and ceramide 29 .…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, interfacial elasticity has been shown to be lowest for the Lo phase, when compared to that of liquid-condensed (~gel) or liquid-expansed (~fluid) phases of sphingomyelin monolayers [75]. In bilayers made of red blood cell lipid extract, García-Arribas et al [76] measured as low breakthrough forces as those of a fluid phase, even though the bilayers were expected to be in Lo phase due to their cholesterol content.…”
Section: Role Of Phase State On the Young Modulus Of Milk-sm Bilayersmentioning
confidence: 99%
“…Meanwhile, the human erythrocyte membrane contains up to 45 mol% of cholesterol [82,83]. Even though the distribution and fluxes of cholesterol in cells are complex [84], this indicates that gel phase is probably inhibited in many biologically relevant situations, even though indirect observations pointed to some gel phase domains in the MFGM [15], not to mention the role of other compounds like ceramides [76]. The high amounts of cholesterol in plasmatic membranes, compared to those used in model vesicle or supported membranes, may account for the lower Young modulus values generally found when directly probing cells or milk fat globules.…”
Section: Role Of Phase State On the Young Modulus Of Milk-sm Bilayersmentioning
confidence: 99%
See 1 more Smart Citation